2021
DOI: 10.21203/rs.3.rs-266260/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Breast Cancer Risk factors in Relation to Molecular Subtypes in Breast Cancer Patients from Kenya.

Abstract: BackgroundFew studies have investigated risk factor heterogeneity by molecular subtypes in indigenous African populations where prevalence of traditional breast cancer (BC) risk factors, genetic background, and environmental exposures show marked differences compared to European ancestry populations. MethodsWe conducted a case-only analysis of 838 pathologically confirmed BC cases recruited from 5 groups of public, faith-based and private institutions across Kenya between March 2012 to May 2015. Centralized pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
(22 reference statements)
0
4
0
Order By: Relevance
“…All WRA in Turbo sub-county were targeted because the increased risk of BC has been associated with changes in reproductive patterns including a shorter period of breastfeeding and low parity [14]. Additionally, Sayed et al, found out that among the diagnosed cases of BC in Kenya, almost 16 were aged below 25 years indicating the need for further research in this understudied age category [15].…”
Section: Target Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…All WRA in Turbo sub-county were targeted because the increased risk of BC has been associated with changes in reproductive patterns including a shorter period of breastfeeding and low parity [14]. Additionally, Sayed et al, found out that among the diagnosed cases of BC in Kenya, almost 16 were aged below 25 years indicating the need for further research in this understudied age category [15].…”
Section: Target Populationmentioning
confidence: 99%
“…In 2020, Kenya had a 5-year prevalence of BC of 57.28 per 100 000 (15,496) leading to 23% of all cancer cases [1]. In the same year, 6,799 (16.1%) new cases of BC were diagnosed and 3,107 (11.5%) deaths due to BC recorded [6].…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Acrosssectional study and the meta-analytical procedure were used to assess the risk factors and preventive measures regarding the carcinoma breast. [7][8][9] A case control study was conducted in Saudi Arabia on breast cancer survivors' perceptions of prevention versus control of future cancer recurrence. 10 Most of research on carcinoma breast were followed the cross-sectional study and use of structured questionnaire to assess the knowledge of risk factors and preventive measures of carcinoma breast.…”
Section: Introductionmentioning
confidence: 99%
“…Given that both parity and breastfeeding are higher in Ghana compared to the US, it is unclear if these factors could contribute to differences in ERN rates across countries [17]. Whether biological, behavioural or social/environmental factors contribute to higher incidence rates of ERN tumours in women of SSA origins requires further investigation [1, 18], especially since data support different distributions of breast cancer subtypes in Kenya [19], South Africa [20] compared to Ghana [17]. In contrast, ERP breast cancer incidence remains low in Ghana compared to US NHB or NHWs.…”
mentioning
confidence: 99%